Den of iniquity [large type] - Jance, Judith A. (Jance, Judith A. J. P. Beaumont mysteries, 2024)
Former Seattle homicide cop J. P. Beaumont faces trouble in the small town of Ashland, as both his personal and professional lives are thrown into turmoil. Beau's daughter and son-in-law are having marital troubles, and his grandson, a senior in high school, shows up on his doorstep, wanting to live with Beau and his wife Mel as he finishes out the school year. Meanwhile, a friend from his past asks for Beau's help in looking into what appears to be an accidental death. A young man died of a fentanyl overdose, but those closest to him are convinced that he would never have used the drug, and that something much more sinister has happened. Beau agrees to unofficially reopen the case, and his investigation leads him to uncover similar mysterious deaths that all point to a most unlikely suspect. As the case becomes more complicated than he could have imagined, and past and present mysteries collide, it will take everything Beau has to track down a dangerous vigilante killer.